Woodwind Quintet Op. 26 (Schoenberg's Twelve-Tone Music, 2014)
Immune checkpoint inhibitors (ICIs) have reshaped modern oncology by improving outcomes in multiple cancers. They function by enhancing T-cell-mediated antitumor immunity through the blockade of inhibitory pathways, such as cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), the PD-1 receptor and its ligand PD-L1, and lymphocyte-activation gene 3. Despite their clinical benefits, ICIs are associated with immune-related adverse events that can involve any organ system. Renal toxicity, although less common, represents a clinically important and often underrecognized complication with substantial morbidity and health care costs. The pathogenesis of immune-related acute kidney injury (irAKI) is thought to be primarily immune-mediated, driven by unchecked T-cell activation and loss of peripheral tolerance within the kidney. Clinically, irAKI is often asymptomatic and often detected incidentally as a rise in serum creatinine. Diagnosis is largely one of exclusion, requiring careful evaluation for alternative causes of AKI common in oncology patients. Management is guided by AKI severity and revolves around the temporary or permanent discontinuation of ICIs, prompt initiation of corticosteroids, and additional immunosuppressive therapy reserved for refractory cases. This review summarizes current evidence on ICI-associated AKI and highlights areas where further prospective research is needed to optimize both renal and oncologic outcomes.